Shared signaling pathways and comprehensive therapeutic approaches among diabetes complications - Ebrahimi, Moein; Ahmadieh, Hamid; Rezaei Kanavi, Mozhgan; Safi, Sare; Alipour-Parsa, Saeed; Advani, Soroor; Sorenson, Christine M.; Sheibani, Nader (Frontiers in Medicine, 2025)
The growing global prevalence of diabetes mellitus (DM), along with its associated complications, continues to rise. When clinically detected most DM complications are irreversible. It is therefore crucial to detect and address these complications early and systematically in order to improve patient care and outcomes. The current clinical practice often prioritizes DM complications by addressing one complication while overlooking others that could occur. It is proposed that the commonly targeted cell types including vascular cells, immune cells, glial cells, and fibroblasts that mediate DM complications, might share early responses to diabetes. In addition, the impact of one complication could be influenced by other complications. Recognizing and focusing on the shared early responses among DM complications, and the impacted cellular constituents, will allow to simultaneously address all DM-related complications and limit adverse treatment impacts. This review explores the current understanding of shared pathological signaling mechanisms among DM complications and recognizes new concepts that will benefit from further investigation in both basic and clinical settings. The ultimate goal is to develop more comprehensive treatment strategies, which effectively impact DM complications in multiple organs and improve patient care and outcomes.